Integrated model of product manufacturing cycle time estimation - Todic, Vladimir (Journal of Production Engineering, 2023)
In modern business conditions, companies engaged in individual and small-batch production are faced with one of the key tasks of production management, which refers to weekly and, very often, daily production planning. Short delivery times, limited prices, and high requirements regarding the quality and method of product delivery all require timely planning of production capacities, tools, and devices, as well as the number of workers and their allocation to individual jobs. In such production conditions, which are determined by the market, it is of particular importance to determine the production time of the product quickly and qualitatively, including the production price, within the framework of making an offer according to the customer’s demand. The paper presents a cycle time estimation model as a part of the overall product manufacturing time, using ANN and fuzzy neural networks.